Entre telespectador e usuário: continuidades, rupturas e transformações na plataforma Globoplay em uma perspectiva da tecnocultura audiovisual - Cândido, Raiana Garay (Universidade do Vale do Rio dos Sinos, 2024)
This research investigates the development processes of the Globoplay streaming platform from the perspective of audiovisual technoculture, with special attention to the tensions established in the relationship between viewer and user. The aim is to present the interfaces of Globo's video platforms in different phases, focusing on television memory and the changes in the relationship between the broadcaster and its audience. To do this, we adopted a methodology based on media archaeology (Fischer, 2008; Huhtamo, 1997), using the practice of excavation as a means of understanding the characteristics of the media. We represent this analysis in layers, addressing Design, Television Memory and Technoculture. This metaphorical approach, inspired by geological layers, aims to recover old interfaces by excavating the company's official websites and the Wayback Machine. This perspective made it possible to go through journeys that reveal video insertions in the company's main digital projects, prioritizing observation in the television memory phase (KILPP, 2005). The analysis of the layers included temporal divisions, represented by a timeline that points to the past, present and future, and was carried out in two stages: a first round that allowed the problematization to mature and a second round that was structured around the construction of the user, interface/platform and television memory layers. The study considered concepts of continuities, ruptures and transformations to identify the evolution of the relationship between the broadcaster and the public.In addition, interviews were conducted with Globo Digital Hub users and professionals, as well as a brief comparative experiment.Conceptually, the research sought to dialogue with audiovisual technoculture (TCAV, 2013) and communication studies (Cannito, 2010; Jenkins, 2009; Shirky, 2011), also using the concept of platformization (Van Dijck, 2018).With regard to the use of interfaces, contributions from Human-Computer Interaction (Manovich, 2001; Norman, 1998) and Interaction Design (Roger, Sharp & Preece, 2013) were incorporated.
Keywords: Globoplay; Plataformização; Telespectador-usuário; Audiovisualidades; Arqueologia da mídia; Platformization; Viewer-user; Audiovisualities; Media archaeology; ACCNPQ::Ciências Sociais Aplicadas::Comunicação